The effect of celecoxib on kidney function in elderly people in the Saudi health sector - Al-Khulaifi, Hela Saleh; Al-Mutairi, Tala Saeed; Al-Battal, Norah Ibrahim (Journal of medical and pharmaceutical sciences, 2024)
The aim of this research is to evaluate the impact of celecoxib on kidney function among elderly individuals within the Saudi healthcare system. The study's target population comprises kidney patients residing in Riyadh. Given the challenges associated with conducting a comprehensive inventory of all individuals within this population, the research employed a sampling approach. Specifically, a simple random sample of patients was selected from both the King Salman Center for Kidney Disease and the Dialysis Center at Diriyah Hospital, resulting in a total of 150 participants in the study sample. To collect data, an electronic questionnaire will be utilized, and the respondents will consist of kidney patients in Riyadh. Data analysis will be conducted using SPSS23.  Findings from the study indicate potential adverse effects of NSAIDs on renal health. In conclusion, the use of NSAIDs, by inhibiting the inflammatory response mediated by COX enzymes, which forms the fundamental approach to managing pain and fever, may expose patients to harmful and hazardous kidney-related side effects. Therefore, it is imperative for healthcare practitioners to exercise caution when prescribing short-term celecoxib medication, as it has been associated with significant or life-threatening renal failure in patients with both normal and impaired renal function. Patients with severe renal conditions should avoid the use of celecoxib altogether.
Keywords: NSAIDs; celecoxib; kidney; renal; elderly people; old people